2020
DOI: 10.21203/rs.3.rs-105339/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Construction and Validation of a Ferroptosis-Related Prognostic Signature in Kidney Renal Clear Cell Carcinoma

Abstract: Background: Kidney renal clear cell carcinoma (KIRC) is the most common and lethal renal cell carcinoma (RCC) histological subtype. Ferroptosis is a newly discovered programmed cell death and serves an essential role in tumor occurrence and development. The purpose of this study is to analyze ferroptosis-related gene (FRG) expression profiles and to construct a multi-gene signature for predicting the prognosis of KIRC patients.Methods:RNA-sequencing data and clinicopathological data of KIRC patients were downl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In cancer cells, GLS2 upregulation can induce an antiproliferative response with cell cycle arrest (47). Notably, high expression of risk genes, such as CD44, FANCD2 and CHAC1 as well as low expression of NCOA4 were found to be correlated with worse OS in KIRC (21,22), in line with our results. Taken together, these genes may be involved in KIRC via involved in ferroptosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In cancer cells, GLS2 upregulation can induce an antiproliferative response with cell cycle arrest (47). Notably, high expression of risk genes, such as CD44, FANCD2 and CHAC1 as well as low expression of NCOA4 were found to be correlated with worse OS in KIRC (21,22), in line with our results. Taken together, these genes may be involved in KIRC via involved in ferroptosis.…”
Section: Discussionsupporting
confidence: 90%
“…Ferroptosis-related genes such as BRCA1-associated protein 1 (BAP1) (17), nuclear factor erythroid 2-related factor 2 (NRF2) (18,19), and glutathione peroxidase 4 (GPX4) (20) are found to be implicated in tumorigenesis and progression. Although recent studies have revealed that some ferroptosis-related genes, such as Cystathionine beta-synthase (CBS), CD44, Fanconi anemia complementation group D2 (FANCD2), glutamate exchanger xCT (SLC7A11) are associated with high-risk patients with KIRC (21,22), the key ferroptosis-related genes that could predict clinical prognosis and tumor immunity in KIRC have not been fully discovered.…”
Section: Introductionmentioning
confidence: 99%